Analysis of Software Quality Needs in Mobile-based Game Software - Ajeng Casika; Suroso Suroso; Ipang Sasono; Tias Pramono; Masduki Asbari (Edumaspul: Jurnal Pendidikan, 2022)
The game is composed of rules with interesting scenarios as well as audio-visuals for entertaining users. With the development of mobile devices, games have also emerged on mobile devices. Thus it takes a quality model that every game developer expects. The characteristics of mobile game software are more unique than gaming software in general, especially in terms of mobility and portability. The quality of a mobile game can be seen from the aspects measured and tested according to the metrics for the quality needs of the mobile game. To determine the quality needs of the software, the characteristics of the software are used so that it becomes the basis for the formation of quality needs that are by the case used. The quality needs for mobile-based games are obtained from the characteristics of mobile-based applications and mobile-based games. Evaluation of the proposed quality needs will be used as a reference to measure the quality of a mobile game.